Renewable energy supply and economic growth in Malaysia: an application of bounds testing and causality analysis - Ahmed Sulub, Yasin; Hamid, Zarinah; Mior Nazri, Mior Nasir (Cag University, Mesin, Turkey, 2020)
Empirical researches on the nexus between renewable energy supply and economic growth have been neglected. To address this gap, this study aims to examine the relationship between hydropower energy supply (HES) and economic growth within a multivariate model for the 1978-2017 period. This study utilized the auto regressive distributive lag (ARDL) bounds approach to testing for cointegration relationship; and the Granger causality test, based on the vector error correction model (VECM) to test for causality. The bounds F-test for cointegration shows that HES, electricity consumption, capital formation and GDP growth share a long-run relationship. Results show that HES has a significant positive impact on economic growth in the short-run. The causality tests yield evidence of unidirectional long-run and short-run causality running from economic growth to HES, suggesting that economic growth is necessary for providing the essential resources for fostering the HES. The existence of cointegration among HES and GDP growth infers that HES will not drift too far away from economic growth in the long-run. Thus, the government needs to ensure a sufficient supply of hydropower energy in the short-run and the long-run.